2012
DOI: 10.3109/17482941.2012.741244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Impella and intra-aortic balloon pump in high-risk percutaneous coronary intervention: Vascular complications and incidence of bleeding

Abstract: Impella can be used as safely as IABP during high-risk PCI with similar vascular and bleeding complications. Importantly, approximately one third of bleeding was from the gastrointestinal system warranting careful prophylactic measures and monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…In the controlled observational studies, the 30‐day rates of all‐cause mortality were higher in the Impella arm than in the IABP arm in 2 of the 3 studies that reported this endpoint (Table ) . However, neither reached statistical significance due to their modest sample sizes.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In the controlled observational studies, the 30‐day rates of all‐cause mortality were higher in the Impella arm than in the IABP arm in 2 of the 3 studies that reported this endpoint (Table ) . However, neither reached statistical significance due to their modest sample sizes.…”
Section: Resultsmentioning
confidence: 96%
“…Several studies have examined the effectiveness and safety of the Impella device . However, many of these studies were small and produced inconclusive results.…”
Section: Introductionmentioning
confidence: 99%
“…A single-center study of ECLS in cardiogenic shock reported bleeding complications in 17.4% and need for surgical intervention in 8.7% of all patients [23] while registry data for ECLS in cardiopulmonary resuscitation report complications directly related to ECLS implantation in every third patient [16]. Concerning blood transfusions after device implantation, a recent meta-analysis reported a transfusion in 32 to 38% of all patients after IABP or Impella 2.5 implantation, respectively [24]. …”
Section: Discussionmentioning
confidence: 99%
“…The major complications of using the device are vascular injury, hemolysis, thrombocytopenia, and impairment of valve function [13,14]. Mild hemolysis was suspected in this case, but it was not severe enough to require early discontinuation of the device, nor blood transfusion.…”
Section: Discussionmentioning
confidence: 94%